EVALUASI SENYAWA BIOAKTIF Nasturtium montanum Wall. SEBAGAI KANDIDAT AGEN ANTIPIRETIK TERHADAP RESEPTOR PROSTAGLANDIN SYNTASE 2 (PTGS2) SECARA IN SILICO [Evaluation of Bioactive Compounds of Nasturtium montanum Wall. as Antipyretic Agent Candidate Toward Prostaglandin Syntase 2 (PTGS2) Through in Silico] - Ikhtira, Dilla Anisa; Rohman , Fatchur; Lestari, Sri Rahayu (Berita Biologi, 2023)
The inhibition of prostaglandin syntase 2 ( PTGS2 route is necessary in order to prevent an feverfever. Antipyretic drugs such as the Non steroids ( NSAIDs are fever medication which acts as non-selective inhibitor of PTGS2. NSAID overdose cases have led to herbal ingredients utilization as alternative remedies, such as the Nasturtium montanum leaves. This research aimed to observe the interaction of selected bioactive compounds within N. montanum with the PTGS2 target protein through molecular docking. In addition, this research used in silico approach conducted with molecular docking method trough several stages such as preparation of 3D ligand structure and protein, protein sterilization by PyMOL, docking compounds with PyRx and visualization of docking results via LigPlot+. Results obtained from this research shows the bond dissociation energy value of 1-O-sinapoyl-beta-D-glucose, kaempferol 3-O-sophoroside, patuletin 3-gentiobioside and quercetin 3-O-malonylglucoside substances are smaller compared to meclofenamic acid causing the four ligand tests more stable in their binding to PTGS2 receptor. Meclofenamic acid and 1-O-sinapoyl-beta-D-glucose both bind to PTGS2 receptor with the same amino acid residue as well as the same interaction. Whereas meclofenamic acid, kaempferol 3-O-sophoroside, patuletin 3-gentiobioside and quercetin 3-O-malonylglucoside bind to PTGS2 receptor with the same amino acid residue yet have different bond interaction.